(untitled) (Circe de clásicos y modernos, 2025)
The heroines of the Euripidean tragedies Medea and Hypsipyle agree on many aspects: they bonded with Jason and had children with him, they are on a foreign land without the supervision of their kyrios and away from their natal oikos. My aim is to analyze how each drama depicts the links between these women, their tutors and their parental homes. For that reason, I study in detail the moment when they drive apart from their fathers and their familiar houses attempting to define whether the different modes of separating foresee the future of their own oikoi and their heirs.